CROSS-BORDER COMPETITION FRAMEWORK: IMPLEMENTATION OF THE EXTRATERRITORIALITY PRINCIPLE IN THE APPLICATION OF COMPETITION LAW IN INDONESIA UNDER LAW NUMBER 5 OF 1999: CROSS-BORDER COMPETITION FRAMEWORK: IMPLEMENTASI PRINSIP EKSTRATERITORIALITAS PADA PENERAPAN HUKUM PERSAINGAN USAHA DI INDONESIA DI BAWAH UNDANG-UNDANG NOMOR 5 TAHUN 1999 - Gaung Aidaferti Zelina CH (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Abstract In the context of the application of business competition law in Indonesia, Law Number 5 Year 1999 has a scope that applies in the territory of Indonesia. This law regulates the prohibition of monopolistic practices and unfair business competition in the country to protect consumers, promote fair competition, and encourage economic efficiency. This research uses the normative juridical method to analyze legal norms and principles. The approaches used include the statutory approach, comparative law approach, and case approach. The analysis shows that Law No. 5/1999 on Competition Law does not regulate extraterritorial jurisdiction for foreign companies. Supreme Court Regulation Number 03 of 2005 and KPPU Regulation Number 2 of 2023 also do not contain extraterritoriality clauses in competition law. This lack of legal certainty will affect the implementation of the decision, even though there is a legally binding decision declaring violations by foreign companies. KPPU cannot execute without a strong legal basis. Indonesian court decisions are only valid in the Indonesian jurisdiction. To carry out competition law enforcement efficiently and effectively, bilateral or multilateral cooperation with other countries is required.